2018
DOI: 10.1039/c8nj00425k
|View full text |Cite
|
Sign up to set email alerts
|

A novel and high performance enzyme-less sensing layer for electrochemical detection of methyl parathion based on BSA templated Au–Ag bimetallic nanoclusters

Abstract: In the present manuscript, a modified glassy carbon electrode with BSA templated Au–Ag bimetallic nanoclusters (Au–Ag@BSA/GCE) was employed for the rapid, selective and sensitive determination of methyl parathion (MP) as an enzyme-less electrochemical biosensor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The intensities of the peaks at 18.9° and 27° were higher for PPS-ZIF-8 and PPS-ZIF-8-BSA than for the ZIF-8 nanocrystals, which might be attributed to the superposition of PPS and ZIF-8 peaks. Compared to PPS-ZIF-8, PPS-ZIF-8-BSA generated an additional peak at 22°, which can be assigned to BSA . As shown in the XRD patterns, the ZIF-8 peaks of PPS-ZIF-8 and PPS-ZIF-8-BSA were shifted to slightly lower 2θ values compared to the spectrum of ZIF-8.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The intensities of the peaks at 18.9° and 27° were higher for PPS-ZIF-8 and PPS-ZIF-8-BSA than for the ZIF-8 nanocrystals, which might be attributed to the superposition of PPS and ZIF-8 peaks. Compared to PPS-ZIF-8, PPS-ZIF-8-BSA generated an additional peak at 22°, which can be assigned to BSA . As shown in the XRD patterns, the ZIF-8 peaks of PPS-ZIF-8 and PPS-ZIF-8-BSA were shifted to slightly lower 2θ values compared to the spectrum of ZIF-8.…”
Section: Resultsmentioning
confidence: 89%
“…Compared to PPS-ZIF-8, PPS-ZIF-8-BSA generated an additional peak at 22°, which can be assigned to BSA. 34 As shown in the XRD patterns, the ZIF-8 peaks of PPS-ZIF-8 and PPS-ZIF-8-BSA were shifted to slightly lower 2θ values compared to the spectrum of ZIF-8. This phenomenon was attributed to increased lattice strain and lattice distortion during nanostructure formation.…”
Section: Methodsmentioning
confidence: 81%
“…203 For example, a series of stimuli-responsive Schiff base-linked hydrogels for applications in biocatalysis and biosensing were reported using both HSA and BSA. 141 BSA has also been incorporated in nanostructure templates for biosensing the insecticide methyl parathion, 204 nanoparticles for controlled CUR delivery, 205 and non-ionic surfactant drug-delivery vesicles. 206 HSA, though being comparatively understudied, may function as a drug carrier due to complexations with antimicrobial and anticancer pharmaceuticals.…”
Section: Albumin Hydrogelsmentioning
confidence: 99%
“…It has been demonstrated that bimetallic nanoclusters of Ag and Au have increased optical properties due to the transfer of load across metals, as well as improved plasma stability and biocompatibility. Because of their ultra-small size and particular electrical structure, they interact better with biological systems [ 37 ]. Xu et al developed an electrochemical biosensor based on AChE immobilization and used it to detect the pesticides methyl parathion, malathion, and chlorpyrifos in cabbage juice, with LODs of 3.04 × 10 −3 ng L −1 , 1.96 × 10 −3 ng L −1 , and 2.06 × 10 −3 ng L −1 , respectively.…”
Section: Dataset Visual Approachesmentioning
confidence: 99%